The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/phm.0b013e31821f6f1f
|View full text |Cite
|
Sign up to set email alerts
|

Are Abnormalities in Sarcoplasmic Reticulum Calcium Cycling Properties Involved in Trapezius Myalgia?

Abstract: These results demonstrate the feasibility of analyzing tissue samples for a wide range of properties and provide a rationale for studies examining the cellular basis of myalgia with particular emphasis on sarcoplasmic reticulum Ca cycling, given the latter's role in regulating a wide range of cellular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…Green et al . have reported decreased Ca‐ATPase activity and expression of both SERCA1a and SERCA2a in patients suffering from trapezius mialgia. In addition, dysfunctions of the calcium pump related to defects in activity or expression have been reported in heart failure, cancer development, and Brody's and Darier's diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Green et al . have reported decreased Ca‐ATPase activity and expression of both SERCA1a and SERCA2a in patients suffering from trapezius mialgia. In addition, dysfunctions of the calcium pump related to defects in activity or expression have been reported in heart failure, cancer development, and Brody's and Darier's diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Although speculatively, this may be related to altered Ca 2+ kinetics of myalgic muscles. Interestingly, Green and coworkers found a compromised sarcoplasmic reticulum Ca 2+ -ATPase activity, Ca 2+ -uptake, and Ca 2+ -release in a case-series study involving women with myalgia [46]. A slower relaxation of myalgic muscles may have negative implications for high pace work tasks where the time for recovery between contractions is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…This modification on the vascular system has been interpreted as orthosympathetic response to pain and it is related with O2 reduced presence and reduction of ATP activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Important anomalies were also observed within the muscle fibers. Three case reports published by Green et al [25] appeared as very interesting to understand intracellular biochemical changes of the myo-fascial syndrome associated with IOMNP. These authors found a decrease of O2, decrease in phospho-kinase activity, decrease [up to 45%] of Ca reuptake within the sarco-plasmatic reticulum, and disruption of ATPhasic Na-K.…”
Section: Histology and Metabolismmentioning
confidence: 99%